Pancreatic Alpha-Cells from Female Mice Undergo Morphofunctional Changes During Compensatory Adaptations of the Endocrine Pancreas to Diet-Induced Obesity - Gonzalez-Figueroa, A (Nature Publishing Group, 2015)
Obesity is frequently associated with insulin resistance. To compensate for this situation and maintain normoglycaemia, pancreatic beta-cells undergo several morphofunctional adaptations, which result in insulin hypersecretion and hyperinsulinaemia. However, no information exists about pancreatic alpha-cells during this compensatory stage of obesity. Here, we studied alpha-cells in mice fed a high-fat diet (HFD) for 12 weeks. These animals exhibited hyperinsulinaemia and normoglycaemia compared with control animals in addition to hypoglucagonaemia. While the in vivo response of glucagon to hypoglycaemia was preserved in the obese mice, the suppression of glucagon secretion during hyperglycaemia was impaired. Additionally, in vitro glucagon release at low glucose levels and glucagon content in isolated islets were decreased, while alpha-cell exocytosis remained unchanged. Assessment of morphological parameters revealed that alpha-cell area was reduced in the pancreas of the obese mice in association with alpha-cell hypotrophy, increased apoptosis and decreased proliferation. HFD feeding for 24 weeks led to significant deterioration in beta-cell function and glucose homeostasis. Under these conditions, the majority of alpha-cell changes were reversed and became comparable to controls. These findings indicate that pancreatic compensatory adaptations during obesity may also involve pancreatic alpha-cells. Additionally, defects in alpha-cell function during obesity may be implicated in progression to diabetes.